The development on the heat and efficiency characterization of triple exposure box type solar cooker / Arman Abdul Rashid - Abdul Rashid, Arman (2010)
The use of solar cooker is much needed in many regions with good solar radiation intensity throughout the world. The reasons are economical, as the price of fuel for cooking is no longer affordable by many families, ecological as in many regions deforestation is also associated with the use of wood as an energy source, and social as the money used to buy fuel could be used to buy foods, medications and other needs to improve the quality of life. This project presents the development on the solar oven, their basic characteristics and experimental procedure to test the triple exposure box type solar cooker. The project's objectives are to determine the heat transfer for the triple exposure of box type solar cooker and the suitability of Malaysia climate for solar thermal. Beginning on the early stage, the researcher will study about the box type solar cooker (also called solar oven). The solar oven needs to collect and trapped the heat inside the box in order to cook the foods. For this reasons, the solar oven is design to have the side that exposed to the sunlight that is made by glass. In this project, the researcher used the triple exposure side of solar oven. The solar even has been tested in order to investigate its performance. Thermocouple and pocket logger XR440 was used to determine the temperature inside the solar oven. As a result, the heat transfer through the solar oven has been determined. The performance of solar oven also been recorded. This result will be used to determine the suitability of Malaysia climate for solar thermal application especially for cooking.